Household vulnerabilities and responses to climatic and socio-economic stressors in Southern African dry forests and woodlands - Paumgarten, Fiona (My University, 2020)
Rural households in the dry forests and woodlands of southern Africa face significant challenges to securing a sustainable livelihood. Climate change will likely exacerbate existing vulnerabilities in these dryland systems, particularly where households depend on climate-sensitive livelihoods and ecosystem services. In line with global goals to reduce and manage the risk of climate change, and to increase the likelihood of achieving the Sustainable Development Goals, there is the need to enhance rural households’ adaptive capacity. Given the southern African region’s broader development challenges, including the existing funding and capacity constraints, adaptation interventions need to be effectively targeted. Although adaptation is described as a multi-dimensional and multi-scale process, the Intergovernmental Panel on Climate Change (IPCC) suggests that national commitments are often undermined by limited understanding of local level responses. A review of the existing literature from across southern Africa indicates limited local-level assessments of the climate-related risk of rural households in the region. A better understanding of the local context, guided by scientific research and local knowledge, is therefore important, particularly to support the design and implementation of appropriate interventions. These adaptation interventions should be cognisant of the heterogeneity of rural communities, acknowledge households’ broader vulnerability context, recognise those groups most likely to be worst affected by climate change, and support households’ existing capacity to respond to stresses and shocks. With the aim of contributing towards an improved understanding of the local context, this thesis explores household vulnerabilities and responses to climatic and socio-economic stressors in southern African dry forests and woodlands. Focusing on two rural communities in South Africa’s Limpopo Province, and taking a livelihoods approach, the study explored various aspects related to the climate-related risk of rural households, local perceptions and experiences of climate change and variability, households’ broader vulnerability context (focusing on a range of stressors, including natural hazards), and their existing coping options (including the safety-net role of natural resources). With respect to the latter, it was assumed that households’ existing coping strategies (and their access to assets) are indicative of households’ adaptive capacity. For each of these aspects the influence of a number of factors, including location, various household characteristics, and households’ existing capital portfolio, was considered. Data were collected through a mixed-method approach, which included household surveys and a detailed Participatory Rural Appraisal. South Africa’s Limpopo Province, one of the country’s poorest provinces, comprises predominantly rural areas, many of which are located in underdeveloped, former homeland areas. Households in these areas continue to rely on climate-sensitive livelihoods and have low adaptive capacity given limited assets and poor access to economic development opportunities. We considered rural households in the villages of Bennde Mutale and Vondo. Although both villages fall within the same district municipality, sites were selected in different agro-ecological zones, with notable differences in mean annual precipitation. Bennde Mutale falls within a dry agro-ecological zone, while Vondo is located in a semi-arid zone, receiving almost three times Bennde Mutale’s annual precipitation. Households in both villages continue to rely on land-based livelihoods and ecosystem services, including the use and sale of non-timber forest products (NTFPs). Given the heterogeneity of rural households, differential climate change impacts are likely, both within and between communities. To better understand households’ climate-related risk a cluster-based approach was used to identify archetypical climate-risk profiles based on the core components of risk, as defined by the IPCC. The identification of six archetypical profiles allowed for the systematic interpretation of the nature of households’ climate-related risk. The profiles highlight the extent and heterogeneity of risk, with differences noted in the experience of natural hazards, in households’ exposure, the impacts faced, and in households’ adaptive capacity. Two high-, two moderate-, and two low-risk profiles were identified, with almost a third of households categorised as high-risk. These high-risk households continue to rely on land-based livelihoods, have poor access to secure shelter, and have low adaptive capacity, with the exception of access to natural capital. A clear site-related distinction in the profiles suggests adaptation interventions need to be site-specific, with households’ livelihood strategies and capital endowments shaped by the agro-ecological zone. However, the influence of factors such as household age and the gender of the household head, indicates that interventions aimed at improving households’ adaptive capacity need to also account for socio-demographic characteristics. These insights provide lessons for the development and targeting of interventions aimed at supporting local-level adaptation. The profiles provide a baseline against which interventions can be monitored. The identification of distinct climate-risk profiles supports the design and implementation of adaptation interventions however questions remain on how best to cultivate local-level adaptation. Concerns include that households’ willingness to adapt, and their adaptation responses, may be influenced more by the changes perceived, than the actual climate trends, with the risk of maladaptation. Understanding what factors shape perceptions may help in the design and targeting of more applicable climate change communications and interventions for the development of climate-resilient communities. Within this context, local experiences and perceptions of climate change were explored. Using existing meteorological datasets, the mean, trend and variability in precipitation and temperature as well as the occurrence of significant natural hazards were described. Local perceptions were assessed to determine whether these reflect the data and whether they are consistent, within and between the communities. While changes in precipitation and temperature were widely perceived, these perceptions tended to differ from the meteorological data, with respondents inclined to perceive more challenging conditions. Natural hazards were well remembered, with compelling oral narratives associated with these. These natural hazards result in cognitive biases which influence perceptions, with the risk that future adaptation responses may account only for the extremes not the trends. As with the climate-risk profiles, perceptions diverge by location although they are not uniform within each site. At the site-level, perceptions diverge, influenced by households’ engagement in land-based livelihoods, their access to irrigation equipment and weather information, and their experience of climate-related challenges Although lessons can be learnt from these nuanced perceptions, the intra- and inter-site differences suggest the need for caution in using perception-based studies for one location or group to guide broader adaptation planning. The divergent perceptions intimate the need for targeted climate change communications which support households’ ability to make strategic, long-term adaption decisions. Within the context of climate change and given the need for households to improve their adaptive capacity, there has been renewed interest in households’ existing coping strategies, including the safety-net function of NTFPs. It has been suggested that strengthening households’ existing coping portfolio is a means of facilitating adaptation, and important given households’ broader vulnerability context. Better understanding households’ past responses to climate-related and other shocks, their existing coping options, how households combine and protect these options, and the opportunities and constraints associated with these, may provide insights into enhancing households’ adaptive capacity. Within this context the range and prevalence of unanticipated shocks experienced by rural households, and the coping strategies used in response to these, was considered. Using mosaic plots to highlight associations between the shocks experienced and strategies used, it was investigated whether households apply coping strategies arbitrarily or not. A multivariate analysis was used to explore the influence of site and/or household characteristics on the adoption of a strategy. Households are exposed to various unanticipated production, human and financial shocks, as well as natural hazards, with production shocks being the most common. Although they rely on various informal coping strategies, these are applied selectively depending on the shock and on households’ intent to manage their future options. Households’ coping choices are also influenced by their access to human and financial capital. Households rely on social and natural capital to protect their alternative coping options, suggesting that a reliance on these capitals is not necessarily an indicator of limited alternatives. Households’ informal, ex-post coping strategies appear to be limited for natural hazards, with households relying instead on external assistance or on ex-ante household savings. More vulnerable households were less likely to rely on external assistance, suggesting barriers to these social safety-nets. Households’ reliance on savings is concerning. Increasingly frequent and intense natural hazards may hinder the accumulation of savings, undermining households’ efforts to secure a sustainable livelihood, and reducing their capacity to cope and adapt. Natural products (specifically NTFPs) were not often used to cope with natural hazards, suggesting limitations to this coping option for covariate, climate-related shocks. Given increasing expectations of the contribution of NTFPs towards sustainable, climate-resilient livelihoods in these dryland areas, there is the need for a more nuanced understanding of this livelihood, coping, and adaptation option. Although households use and sell a diversity of NTFPs, the daily- and safety-net function of wild foods was examined in more detail. In more marginal areas, where crop failure and recurrent drought undermine food and nutritional security, climate-resilient wild foods may play a key role in adaptation. To better understand the potential and limitations of wild foods, households’ consumption of wild edible herbs, fruits and bushmeat, both on a regular basis and in response to increasing food scarcity, was investigated. Wild food consumption is generally prevalent, implying widespread need or that these foods are consumed in response to availability, dietary preferences, and cultural traditions. The sale of wild foods is less prevalent than their consumption. Wild food use is not generic, varying by location, depending on households’ size and existing livelihood strategies. The frequency of wild food consumption during three food availability periods: when food is generally plentiful (e.g. post-harvest); when food is scarce (e.g. during seasonal crop shortfalls); and during “hungry periods” (e.g. drought), was considered. Based on this, three archetypes (clusters) of wild food users were defined, indicating differential dependence on wild foods. Alarmingly, those households who consume wild foods regularly, who were therefore considered to be “wild food dependent”, decreased their consumption frequency under conditions of increasing food scarcity. This suggests that for these “Dependence” households, wild foods constitute a poverty trap, not a safety-net. Seasonal variations in wild food availability, and decreased availability during natural hazards, suggest limitations to the safety-net function of wild foods. Under these conditions, “Dependence” households, characterised by labour-constraints, may struggle to maintain their usual consumption levels, particularly if other households turn to wild foods as a safety-net, increasing competition for limited resources. Although there is the need to recognise the opportunities associated with wild foods, as both a coping and adaptation option, it is also necessary to recognise that under certain circumstances the safety-net function of wild foods may be weak or detrimental to the livelihoods of the most vulnerable. Rural livelihoods in the dry forests and woodlands of southern Africa are inherently vulnerable, particularly given their ongoing reliance on climate-sensitive, land-based livelihood strategies, and their low levels of adaptive capacity. Within the context of climate change, in order to avoid increasing levels of vulnerability and climate-related risk, there is the need to support households’ efforts to cope and adapt. Adaptation and development interventions need to account for the heterogeneity of vulnerability and climate-related risk at the local level, recognising differences in exposure and in households’ existing capacity to cope and adapt. Given the apparent influence of site (and potentially agro-ecological zone) on households’ climate-related risk, their experiences and perceptions of climate variability and change, and on their existing capacity to cope and adapt, these interventions should be site-specific. This study considered two villages within the same district municipality, suggesting that even at the municipal-level, there is the need for nuanced interventions. Wider testing of the methods and frameworks used in this study is recommended to determine if the patterns identified here are repeated across a broader area. This would help in the wider targeting of appropriate interventions. Households’ vulnerabilities and responses, and to a lesser degree, their perceptions of climate change, are also influenced by various socio-demographic and -economic characteristics, emphasising the heterogeneity of rural communities. Interventions need to account for this heterogeneity and recognise that certain households may face barriers to pursuing certain adaptation options. Natural capital is one of the few capital types available to poorer, more high-risk households, however their reliance on this may constitute a poverty trap in the case of natural hazards. This study contributes to our overall understanding of household vulnerabilities and responses to climatic and socio-economic stressors in the dry forests and woodlands of southern Africa. In doing so, it contributes towards addressing the current dearth of such local-level assessments in the region. It provides recommendations for future research, and for policy and practice interventions aimed at enhancing rural households’ capacity to cope and adapt, with this improved capacity identified as a vital target of the Sustainable Development Goals
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg in fulfilment of the requirements for the degree of Doctor of Philosophy, 2020